2018
DOI: 10.3389/fpsyg.2018.01726
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity and Psychometric Properties of the Hebrew Version of the City Birth Trauma Scale

Abstract: As many as third of the women perceive their childbirth as traumatic and although prevalence rates vary between studies, around 2–5% of women in community samples may develop childbirth-related postpartum post-traumatic stress disorder (PPTSD). The City Birth Trauma Scale (BiTS) was developed to address the need for a DSM-5-based instrument that assesses PPTSD. The BiTS is a self-report questionnaire, which covers all DSM-5 PTSD criteria, including the four symptom clusters – re-experiencing, avoidance, negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 49 publications
20
59
1
Order By: Relevance
“…Three items from the Negative cognitions and mood cluster loaded on the factor of Birthrelated symptoms, and the rest of the items loaded on the General symptoms factor. This is similar to previous validation studies Handelzalts et al, 2018).…”
Section: Validation Of the City Bits 15supporting
confidence: 92%
See 3 more Smart Citations
“…Three items from the Negative cognitions and mood cluster loaded on the factor of Birthrelated symptoms, and the rest of the items loaded on the General symptoms factor. This is similar to previous validation studies Handelzalts et al, 2018).…”
Section: Validation Of the City Bits 15supporting
confidence: 92%
“…More specifically, women who had birth by instrumental vaginal delivery and emergency section had significantly higher levels of Birth-related symptoms. This is consistent with the validation of the Hebrew version of the City BiTS in postpartum women in Israel (Handelzalts et al, 2018), with the exception that in the latter study only women who underwent the emergency section reported higher levels of symptoms.…”
Section: Validation Of the City Bits 15supporting
confidence: 88%
See 2 more Smart Citations
“…The original psychometric study, conducted with 950 postpartum women, showed bifactorial structure (birth-related/general symptoms), excellent reliability (α = 0.92) and a high association with distress, unpaired functioning, and desire for treatment (r = 0.50-0.61) 10 . Other than that, it had already been translated and validated into Hebrew 11 and Croatian 10 , in which their psychometric qualities were also replicated.…”
Section: Introductionmentioning
confidence: 99%